Full-duplex mmWave communication with partially-connected hybrid beamforming - Andrea Guamo-Morocho; R. López-Valcarce (IEEE 25th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2024)
Despite the potential of beamforming approaches to mitigate self-interference (SI) in multiantenna mmWave full-duplex (FD) systems, limitations imposed by practical hybrid beamforming architectures make the problem quite challenging. We present a novel design for the partially-connected array structure with finite-precision phase shifters, based on maximizing the product of the signal-to-SI-plus-noise ratios (SSINR) at receivers. Analog precoders and combiners are designed first under this criterion, with SSINR measured at the analog combiners' output. Using the effective channels for the found analog beamformers, the baseband beamformers are then obtained using the same criterion, but with SSINR measured at the digital combiners' output. Simulation results show that the proposed scheme outperforms existing FD approaches in terms of spectral efficiency and residual SI, even with low-resolution phase shifters.
Keywords: full duplex; mayte; mmWave